Meningkatkan Kesadaran Budaya Dalam Pendekatan CRT (Culturally Responsive Teaching) Pada Pembelajaran Sejarah Di Kelas X 1 SMA Negeri 1 Medan Tahun Pelajaran 2023/2024 - Simatupang, Putri Novianti (LPPPI Publishing, 2024)
This research aims to increase cultural awareness in class X 1 students at SMA Negeri 1 Medan through a culturally responsive teaching approach to history learning material. This research uses Classroom Action Research (PTK) with several stages including: planning, action or implementation, observation and reflection. The subjects of this research were 23 class X 1 students at SMA Negeri 1 Medan using quantitative data analysis. The research results showed that cycle I provided an explanation of local history material to students. In applying local history material, students ask questions about the material so that it fosters students' curiosity. Cycle II provides exposure to local historical material as well as carrying out vlog assignments to visit historical buildings to increase cultural awareness. From the results obtained, 43.5% of students gave their cultural awareness a slight increase while 56.5% of students gave the answer that their cultural awareness increased slightly.